Association between Socio-demography/Behavioural Characteristics and Pre-diabetes: A hospital-based comparative study of adult patients - NDUDIM O. OKEZIE,; CHIJIOKE S. ANYIGOR-OGAH,; NNAEMEKA C. OGUEJIOFOR,; IKECHUKWU H. AMAZUE,; UDOCHUKWU D. AGHOR5,; AGATHA N. EKECHI,; HOPE U. OBOKE,; OKECHUKWU ANYIGOR-OGAH,; AUGUSTINA C. ANYIGOR-OGAH, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Pre-diabetes is a condition in which blood glucose levels in humans are higher than normal but not yet in the diabetic range. This condition is not routinely screened for in primary careclinics by health care providers. Aim: To evaluate the association between socio- demographic/behavioural characteristics and pre-diabetes. Method: It is a cross-sectional, comparative study of 100 participants, selected via a systematic random sampling using pretested interviewer administered questionnaire. Participants were recruited by consecutive continuous selection and matched for age and sex. Data was analysed using SPSS Version 23. Results: The result revealed pre-diabetes prevalence of 10.3%. Education (P=0.004), occupation (P=0.005) and social class (P=0.001) had significant association with pre-diabetes. Also, smoking (P=0.007), use of snuff (P=0.003) and physical activity (P=0.001) had significant association with pre-diabetes. Education, occupation and social class status, smoking, use of snuff and physical activity were independently associated with pre-diabetes. Conclusion: The above characteristics were independently associated with pre-diabetes. Clinicians should have high index of suspicion of abnormal glucose level in persons with these factors and institute measures for early detection and interventions, to delay progression to overt diabetes mellitus. Keywords: Socio-demography, Behavioural characteristics, Pre-diabetes